2010
DOI: 10.1007/s10404-010-0580-9
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell microfluidic impedance cytometry: a review

Abstract: Lab-on-chip technologies are being developed for multiplexed single cell assays. Impedance offers a simple non-invasive method for counting, identifying and monitoring cellular function. A number of different microfluidic devices for single cell impedance have been developed. These have potential applications ranging from simple cell counting and label-free identification of different cell types or detecting changes in cell morphology after invasion by parasites. Devices have also been developed that trap sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
417
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 491 publications
(420 citation statements)
references
References 121 publications
(130 reference statements)
3
417
0
Order By: Relevance
“…This opens the route to a possible integration of a Coulter counter unit on chip. Coulter counters integrated with micro fluid systems have been reported previously (18)(19)(20)(21) and on-going work in our group now targets the development of a microfluidic system with integrated acoustophoretic and Coulter counter functionality.…”
Section: Resultsmentioning
confidence: 99%
“…This opens the route to a possible integration of a Coulter counter unit on chip. Coulter counters integrated with micro fluid systems have been reported previously (18)(19)(20)(21) and on-going work in our group now targets the development of a microfluidic system with integrated acoustophoretic and Coulter counter functionality.…”
Section: Resultsmentioning
confidence: 99%
“…[109][110][111] More details on DEP and ROT models can be found in other reviews. 9,112 The most popular ROT setup uses four electrodes connected to sine waves in phase quadrature. 91,113 Cells are placed in the center of the four electrodes (e.g., using laser tweezers).…”
Section: Electrorotationmentioning
confidence: 99%
“…130 More details on impedance flow cytometry can be found elsewhere. 112,130 In addition to coplanar and parallel facing electrode designs, Mernier et al demonstrated ''liquid electrodes'' to discriminate living and dead yeast cells (see Fig. 4(c)).…”
Section: Impedance Flow Cytometry (Ifc)mentioning
confidence: 99%
“…DEP, integrated within microfluidic systems, is more applicable to the manipulation and separation of single cells than their analysis [19,20]. In contrast, EIS enables the frequency-dependent multiparameter readout of cellular and even subcellular information in a high-throughput setting [21,22] or dynamically [23]. EIS provides information related to the cell size at lower frequencies (from hundreds of kHz to MHz), related to the cell membrane capacitance at higher frequencies (several MHz), and information on intracellular features at even higher frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic devices with integrated EIS functions have been developed already for singlecell analysis in the past decade [13,14,21]. Most of those microfluidic devices, called electrical impedance cytometers, were used to characterize suspended biological samples in a flow-through setup.…”
Section: Introductionmentioning
confidence: 99%